Exploring Financial Inclusion in Emerging Economies: Perspectives from Tamil Nadu, India - Ananthy, Y. Jenusha; Asha, Dr.K.; Christopher, Dr.S. Edmund (Indian Journal of Information Sources and Services, 2026)
This research aims to provide recommendations for enhancing financial education programs linked to the Pradhan Mantri Jan Dhan Yojana (PMJDY), targeting financial institutions, government bodies, and policymakers. The findings aim to promote financial inclusion, enhance financial literacy efforts, and promote secure banking practices. In the case of India, a developing country, there has been a unique trajectory in addressing financial inclusion and alleviating instances of financial exclusion. Even while the economy has grown substantially over the last decade, not everyone has benefited from it. Even if advances like mobile phones, online shopping, and round-the-clock financial services are available to many people in cities, many individuals, particularly in rural areas, lack access to these conveniences. Problems with second-generation reforms, especially those involving the financial sector and its attempts to achieve broad financial inclusion, are a contributing factor to India’s uniquely concentrated economic growth. This essay explores the severity of financial exclusion in Tamil Nadu. The purposes of the research include determining the level of financial exclusion in the state, assessing the success of the Reserve Bank of India’s (RBI) initiatives to broaden access to financial services, and identifying the necessary